Análisis de las políticas públicas para el manejo de la informalidad laboral en Bogotá, caso: vendedores ambulantes en el período 2008-2015 (2019)
In this work we seek to differentiate the different public policies implemented in the Development Plans of the mayors Samuel Moreno and Gustavo Petro respectively, for the management of street vendors. On the other hand, presents a characterization of street vendors in the city of Bogotá with which the greatest problems, vulnerability and relocation will be identified of this informal sector of the economy. The intervention and participation of the Institution for the Social Economy (IPES) as the controlling entity in the period 2008-2015.